2004
DOI: 10.1143/jjap.43.5239
|View full text |Cite
|
Sign up to set email alerts
|

GaN/Mirror/Si Light-Emitting Diodes for Vertical Current Injection by Laser Lift-Off and Wafer Bonding Techniques

Abstract: A p-side-up GaN/mirror/Si light-emitting diode (LED) for vertical current injection has been fabricated by laser lift-off and wafer bonding techniques. A variety of metallic mirrors (Au, Al, and Ag) were chosen to improve the optical reflectivity and contact resistance with n-GaN. The GaN/mirror/Si LED with a silver mirror achieved a maximum luminance intensity of 45 mcd (20 mA) with a low forward voltage of 3.5 V. This luminance intensity is over two times that of the original planar GaN/sapphire LED. Under h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…According to this formulation, the output intensity in the external medium is given by (2) where is the "anti-node" factor which results from the twobeam interference from the rear mirror and is the cavity factor (a formulation of the Airy function) due to the presence of the cavity. These are defined respectively as (3) where is the cavity length, is the location of the source from the rear mirror (see Fig. 1), is the internal angle, is the magnitude of the wavevector are the Fresnel reflection coefficients at the air and mirror boundaries respectively (assuming a normal incidence), and is the power transmission at the air boundary.…”
Section: A Scalar Theoretical Model For Back Reflectormentioning
confidence: 99%
See 1 more Smart Citation
“…According to this formulation, the output intensity in the external medium is given by (2) where is the "anti-node" factor which results from the twobeam interference from the rear mirror and is the cavity factor (a formulation of the Airy function) due to the presence of the cavity. These are defined respectively as (3) where is the cavity length, is the location of the source from the rear mirror (see Fig. 1), is the internal angle, is the magnitude of the wavevector are the Fresnel reflection coefficients at the air and mirror boundaries respectively (assuming a normal incidence), and is the power transmission at the air boundary.…”
Section: A Scalar Theoretical Model For Back Reflectormentioning
confidence: 99%
“…In combination these effects lead to extraction efficiencies of the order of [2]. Many methods have been proposed to overcome this fundamental limitation, including adding a metallic rear reflector to the substrate side of the device [3], employing non rectangular parallelepiped chip geometries [4], [5], resonant-cavity devices [6], [7], lens immersion [8], surface patterning [9], surface roughening [10], [11], and two-dimensional surface relief diffraction gratings [12]- [15].…”
mentioning
confidence: 99%
“…Nakada et al reported that considerably higher output power was obtained from a GaInN LED after inserting a DBR between the LED structure and sapphire substrate [1]. Since thin-film laser lift-off (LLO) techniques have recently been developed [2][3][4], GaN-based LEDs fabricated on reflective-metal-mirrorcoated Si substrates by transferring the LED structures from sapphire substrates have been demonstrated [5]. In comparison with this, epitaxial DBR GaN-based LEDs on Si can be grown through one growth process, providing an advantage of a simple process.…”
Section: Introductionmentioning
confidence: 99%
“…The better current spreading of n-GaN can help scale up the chip size without efficiency loss. Third, due to the higher thermal conductivity of the metal alloy substrate, the VLEDMS have much higher heat dissipation capacity [4,7]. Consequentially, higher current operation condition could be achieved, especially for the solid state lighting application.…”
Section: Introductionmentioning
confidence: 99%